INFLUENCE OF SPIRITUAL INTELLIGENCE AND INDIVIDUAL INTELLIGENCE ON PERFORMANCE OF EMPLOYEES AT THE LIBRARY AND ARCHIVES SERVICES OF LAMPUNG PROVINCE - Kristian Astuti; Nur'aeni Nur'aeni; Refi Arioen (University of Sang Bumi Ruwa Jurai, 2023)
There is a problem phenomenon that occurs at the Lampung Provincial Library and Archives Service, namely the inability of employees to serve library visitors with unpleasant attitudes and facial expressions. As well as the sound that is not appropriate when speaking to library visitors. The formulation of the problem in this study is whether spiritual intelligence has an effect on the performance of the employees of the Lampung Province Library and Archives Service, either partially or simultaneously. The purpose of this study was to determine the effect of spiritual intelligence and individual intelligence on the performance of the employees of the Lampung Provincial Library and Archives Service. The hypothesis in this study is that there is an influence of spiritual intelligence and individual intelligence either partially or simultaneously on employee performance at the Lampung Provincial Library and Archives Service. “The sample in this study amounted to 30 employees. Data collection techniques include observation, documentation and questionnaires. The data analysis method uses a quantitative approach with the help of SPSS version 22 statistical tools including the calculation of the validity test, reliability test, simple and multiple linear regression test, t test, F test and coefficient of determination test. The results of hypothesis testing show that spiritual intelligence partially affects employee performance with a contribution of 33.2%. Individual intelligence affects performance with a contribution of 38.3%. Simultaneous hypothesis testing shows that the influence of spiritual intelligence and individual intelligence together has a positive effect on employee performance with a contribution of 51.7%, while the remaining 48.3% is a variation of other variables outside of this study.